2013
DOI: 10.1371/journal.pone.0070878
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Promoter Methylation of VGF and PGP9.5 with Ovarian Cancer Progression

Abstract: PurposeTo elucidate the role of biological and clinical impact of aberrant promoter hypermethylation (PH) in ovarian cancer (OC).Experimental DesignPH of PGP9.5, HIC1, AIM1, APC, PAK3, MGMT, KIF1A, CCNA1, ESR1, SSBP2, GSTP1, FKBP4 and VGF were assessed by quantitative methylation specific PCR (QMSP) in a training set. We selected two genes (VGF and PGP9.5) for further QMSP analysis in a larger independent validation (IV) set with available clinical data. Biologic relevance of VGF gene was also evaluated.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
(67 reference statements)
1
32
0
Order By: Relevance
“…Our initial search yielded a total of 81 potential studies based on the above described search strategy. In the end, 10 case–control studies involving 910 ovarian tissue samples (Agostini et al., ; An et al., ; Brait et al., ; Chmelarova et al., ; Furlan et al., ; Makarla et al., ; Rimel, Huettner, Powell, Mutch, & Goodfellow, ; Roh et al., ; Shilpa et al., ; Wu et al., ) were included in the current meta‐analysis (Figure ). The main characteristics of eligible studies were extracted and shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search yielded a total of 81 potential studies based on the above described search strategy. In the end, 10 case–control studies involving 910 ovarian tissue samples (Agostini et al., ; An et al., ; Brait et al., ; Chmelarova et al., ; Furlan et al., ; Makarla et al., ; Rimel, Huettner, Powell, Mutch, & Goodfellow, ; Roh et al., ; Shilpa et al., ; Wu et al., ) were included in the current meta‐analysis (Figure ). The main characteristics of eligible studies were extracted and shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Further genome‐wide analyses are necessary to improve the sensitivity of the marker set. Of interest might be a combined analyses of poor prognosis markers ( i.e., RUNX3 , CAMK2N1 ) and methylation markers associated with good prognosis ( VGF , PGP9.5) . If such marker sets are successfully validated they may enable the stratification of patients and the selective maintenance treatment with angiogenesis inhibitors, for example, Bevazicumab.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly we also reported previously that UCC can be detected using urine sediment DNA with high sensitivity and specificity [27] and methylation patterns are consistent in primary UCC tissues and urine. Here we found high frequency of methylation of VGF in the urine of UCC cases [8/20(40%)] than controls [1/20(5%)]. We were not able to test methylation status of matched tumor-urine samples due to the lack of available samples.…”
Section: Discussionmentioning
confidence: 69%